Influência socioeconômica do Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) no Estado do Paraná (2012-2017) - Nardi, Alessandro Carlos (2018)
Family farming in Brazil, since the period of colonization, underwent several phases of changes and modifications, and for much of that period there were insufficient resources and credits for this class. The emergence of the National Program for Strengthening Family Agriculture (PRONAF) in 1995 brought family farmers a new spirit and an opportunity to pay for their crops as well as to acquire new inputs to expand their production. In this sense, the objective of this research was to analyze the socioeconomic influence of PRONAF in the State of Paraná between the years of 2012 and 2017. In order to achieve this objective, initially, through bibliographical research the variables studied were extracted and classified according to the productive, social and economic dimensions, being: economic dimension: GDP per capita and Food Acquisition Program (PAA); productive dimension: Gross Value of Production (VBP); social dimension: Family Grant Program, Gini Index and Municipal Human Development Index (IDH-M), in addition to PRONAF variables: Annual average value of contracts and average annual number of contracts. The necessary data were collected on the websites of the Central Bank of Brazil, Ministry of Social Development, Department of Agriculture and Supply / DERAL, Atlas of Human Development and the Brazilian Institute of Geography and Statistics. Then, through the statistical software SPSS©, the correlations, regressions and correspondence analyzes between the variables were performed. Thus, through qualitative and quantitative methods, it was verified that the PRONAF resources are not being directed to the municipalities with the lowest values of the HDI-M, GDP per capita and Gini Index. For the variables Family Allowance and Gross Production Value there was no direct relationship with the volume of PRONAF contracts. For the Food Acquisition Program, in general, the correlation between the average annual value of the contracts and the annual average of the PAA is positive, but weak. It was only possible to prove the impact of PRONAF on the Gross Value of Production in Paraná when multiple linear regression was performed, involving the average value of PRONAF contracts, the annual average of PRONAF contracts, IDH-M and GDP per capita, which shows that the social dimension was the one that presented the greatest positive relation between PRONAF and socioeconomic indicators. The results of the questionnaire indicated that EMATER has the role of disclosure of lines of credit and forms of access, technical guidance and monitoring through reports It is inferred that PRONAF is an important mechanism to support family agriculture, however, according to statistical analyzes, it is verified that the operationalization of the program occurs through insufficient actions to generate effective changes in the socioeconomic situation of the beneficiary public, making the program not reach its full objectives.